Advancing Neurolinguistics in Russia: Experience and Implications of Building Experimental Research and Evidence-Based Practices - Ivanova, Maria V.; Malyutina, Svetlana; Dragoy, Olga (Frontiers in Psychology, 2021)
Russia has rich theoretical and behavioral research traditions in neurolinguistics and neuropsychology, but at the beginning of the 21st century contemporary experimental research in these disciplines remained limited, leading to proliferation of non-evidence-based approaches in education, healthcare, and public beliefs. An academic response to this was the establishment of the Center for Language and Brain at the HSE University, Moscow, which focused on experimental psycho- and neurolinguistic research and related evidence-based practices. The Center has grown from a small group of young researchers to a large interdisciplinary unit that conducts cutting-edge research utilizing multi-site settings and novel structural and functional neuroimaging methods. The overarching aim of the Center’s research is to promote scientifically grounded treatment of the language-brain relationship in the educational, clinical, and industry settings. Specifically, translational research at the Center is contributing to the advancement of clinical practice in Russia: from providing the first standardized aphasia language test to implementing protocols for intraoperative language mapping in neurosurgery departments across the country. Within research projects, a new generation of scientists is successfully being fostered, while a broader student audience is reached via courses taught by staff of the Center to students of different majors. Notable examples of public outreach programs at the Center are the Annual Summer Neurolinguistics School attracting hundreds of attendees from different countries each year, and community projects focused on raising awareness about aphasia. Together, these efforts aim to increase scientific knowledge in a multi-professional audience. In this paper, we will share our joint experiences in establishing, building, and promoting a neurolinguistics research center in Russia and the impact that this work has had on the broader public. We will delineate specific milestones of this journey and focus on the main pillars that have contributed to our progress: research, clinical work, teaching, and public outreach programs. We hope that this critical appraisal of our experiences can serve simultaneously as an inspiration and a practical guide for other groups developing research, clinical and educational programs in different neuroscientific disciplines across the globe and aiming to improve the quality of the neuroscientific information available to the public.